Drug hypersensitivity reactions and allergy in patients with mastocytosis - Czarny, Justyna H.; Lange, Magdalena; Niedoszytko, Marek B.; Kwiecińska, Barbara; Górska, Aleksandra; Ługowska-Umer, Hanna; Sikorska, Monika; Nowicki, Roman (Dermatology Review/Przegląd Dermatologiczny, 2017)
Mastocytosis is a rare myeloproliferative disease caused by excessive proliferation and accumulation of mast cells in the skin and internal organs. The most common variant of mastocytosis in children is cutaneous mastocytosis. Systemic mastocytosis dominates in adults. Both CM and SM patients suffer from mast cell mediator-related symptoms such as itching, flushing, hypotension, abdominal pain, diarrhea, headache and anaphylaxis. The prevalence of anaphylaxis in patients with mastocytosis has been estimated to be about 50% in adults and about 9% in children. Anaphylaxis may be caused by many triggers including hymenoptera sting, drugs, physical factors, exercise, infections, alcohol, some food types and allergens. Drugs which may provoke anaphylaxis include nonsteroidal anti-inflammatory drugs, antibiotics, opioids, contrast media and muscle relaxants. Appropriate preparation of a patient for medical procedures and long-term prophylaxis allow one to reduce the risk of anaphylaxis in patients with mastocytosis.